2006
DOI: 10.1016/j.febslet.2006.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide concentration determines the fate of Ewing's sarcoma family tumors and neuroblastoma cells in vitro

Abstract: Arsenic trioxide (As 2 O 3 ) induces both the differentiation and apoptosis of acute promyelocytic leukemia cells in a concentration dependent manner. We assessed the effects of As 2 O 3 in CADO-ES Ewing's sarcoma (ES), JK-GMS peripheral primitive neuroectodermal tumor (PNET), and SH-SY5Y neuroblastoma cells, as they share common histogenetic backgrounds. As 2 O 3 at low concentrations (0.1-1 lM) induced SH-SY5Y differentiation, and whereas PNET cells acquired a slightly differentiated phenotype, change was mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It has been reported that ATO promotes apoptotic cell death and phosphorylation of JNK [27]. Although western blot analysis showed that ATO treatment increased the amount of phosphorylated JNK, inhibition of JNK activity had no effect on osteosarcoma cell proliferation with or without ATO, as seen with Ewing sarcoma cells (Figure S1) [23].…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that ATO promotes apoptotic cell death and phosphorylation of JNK [27]. Although western blot analysis showed that ATO treatment increased the amount of phosphorylated JNK, inhibition of JNK activity had no effect on osteosarcoma cell proliferation with or without ATO, as seen with Ewing sarcoma cells (Figure S1) [23].…”
Section: Resultsmentioning
confidence: 93%
“…Arsenic concentrations < 1 μM inhibit NF transport into axons in NB2/d1 cells and cultured dorsal root ganglion neurons (DeFuria and Shea 2007). However, some studies have reported that low As concentrations (0.5–1 μM) stimulate neurite outgrowth (Jung et al 2006). One explanation for the observed differences in results is the differing cell culture conditions used during the differentiation treatments, most notably the presence or absence of serum.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether Shank 2 expression is related to the neuronal differentiation via ERK 1/2 activation, we assessed Shank 2 expression in differentiated retinoblastoma cells treated with all-trans retinoic acid (Kim et al, 2007a) and addressed the relationship with ERK 1/2 activation (Jung et al, 2006). As shown in Figure 4A, with treatment of all-trans retinoic acid (10 μM) in SNUOT-Rb1 cells, the expression of neurofilament and Shank 2 were increased together.…”
Section: Shank 2 Expression In Neuronal Differentiation Via Erk 1/2 Amentioning
confidence: 99%